“Voltage control on active networks under adverse conditions.” - SANTOS JÚNIOR, Vicente Tibúrcio (2020)
Due to the inclusion of new loads and the predominant increase in electricity demand associated with the limitations of new environmental projects to minimize carbon emissions, such as pollution resulting from the energy generated by fossil fuels, the incorporation of electrical systems with distributed generation attributes to the energy planning, plans greater efficiency for various sectors of energy consumer groups worldwide. To maintain the effectiveness and reliable operation of the entire power system interconnected between grids and intelligent microgrids of electricity supply, standards must follow the established voltage levels in all terminals of the electrical power supply equipment supply, keeping them within limits. Both power utilities and distributed generation and consumers maintain the required design specifications for a reliable range of variation. The need to maintain a standardized voltage level is summed up in the treatment of possible failures that can occur when there is a voltage level acting beyond the limits established in extended equipment operating times. Due to the failure to maintain constant voltage levels along the electrical power grids several voltage control methods are applied, mainly controlling absorption, production and reactive power flow at all levels of the system, as well as when adverse system conditions where levels can achieve loss of system stability and voltage collapse. This research aims to characterize the appropriate methods for voltage correction and stability in active electrical networks under the influence of adverse conditions, whether natural influences or disasters, to influences related to the conditions of electrical energy systems, such as contingencies and distortions in other factors of the system that influence the level of voltage, to which some scientific publications relate [1-4], analyzing in an equationally calculated experimental way and simulations in MATLAB and ATPDRAW to prove the results.